(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2026)
This study investigates Saudi undergraduate EFL learners’ perceptions of gamified vocabulary learning tools—specifically Kahoot, Quizizz, and Duolingo—in the context of vocabulary retention, learner motivation, and platform usability. Grounded in Self-Determination Theory and the Broaden-and-Build Theory of positive emotions, the study explores how gamification influences learners’ affective engagement and lexical development. A descriptive, cross-sectional survey design was employed, using a structured Google Form questionnaire comprising 10 close-ended items rated on a 5-point Likert scale. A total of 120 Saudi university students participated in the study. Descriptive statistics—means, standard deviations, and percentages—were used to analyze learner responses across three domains: vocabulary retention, motivation, and platform usability. Further, the findings indicate that gamified platforms were positively perceived, with motivation emerging as the most influential factor (M = 4.16), followed by vocabulary retention (M = 3.90), and usability (M = 3.84). Learners reported that game-based elements such as competition, rewards, and instant feedback enhanced their engagement and recall of new vocabulary. Among the platforms, Duolingo was rated most user-friendly for independent learning, while Kahoot and Quizizz were preferred for classroom activities. Despite minor concerns about competition-induced distraction, the overall learner sentiment was highly favourable. These results suggest that gamified tools offer meaningful pedagogical benefits for vocabulary learning in Saudi EFL classrooms. Integrating such platforms into the curriculum may enhance learner engagement, motivation, and retention while aligning with contemporary digital learning preferences.